2004
DOI: 10.1016/j.ejvs.2004.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk of Thrombophilia Defects in Vascular Patients

Abstract: This paper reviews the available data on the prevalence of thrombophilia defects in patients with peripheral vascular disease (PVD) and attempts to delineate the risk of failure of vascular intervention in these patients. The prevalence of thrombophilia in stable claudicants is 25% and increases to 40% in those requiring revascularisation, compared to only 11% in the control group. The overall prevalence of thrombophilia defects in patients with premature atherosclerosis appears to be between 15 and 30%. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Antiphospholipid antibodies were more common in men but did not seem to affect the AVF outcome. High incidence of thrombophilia is reportedly associated with risk of thrombosis after access surgery or revascularization among patients with ESRD and those with other vascular conditions (2,11,14). The difference in thrombophilia prevalence among the studies reflects various definitions of thrombophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Antiphospholipid antibodies were more common in men but did not seem to affect the AVF outcome. High incidence of thrombophilia is reportedly associated with risk of thrombosis after access surgery or revascularization among patients with ESRD and those with other vascular conditions (2,11,14). The difference in thrombophilia prevalence among the studies reflects various definitions of thrombophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Although thrombophilia is attributed to the risk of venous thrombosis and pregnancy complications, it may also contribute to development of arterial disease in relation to the progression of atherosclerosis. 99 Hormone replacement therapy with estrogen is known to increase the risk of venous thrombosis (by 2-to 3-fold), which becomes relevant with aging and presence of thrombophilia. 4 Thus, knowledge of thrombophilia, identified during pregnancy, can lead to better preventive measures during at-risk situations such as surgery, long-distance travel, contraception and hormone therapy use, and subsequent pregnancy.…”
Section: Pregnancy and Opportunities For Primary Preventionmentioning
confidence: 99%
“…[6][7][8][9] Vig et al 10 reported that a quarter of patients with PAD had evidence of thrombophilia. In their other review article, 11 the risk of thrombotic occlusion following arterial revascularization in patients with an identified thrombophilia defect appeared to be almost 3 times that in patients without it. From the present data, the reduced PC activity was a significant determinant factor of CLI.…”
Section: Discussionmentioning
confidence: 97%